Non-linear optical microscopy and histological analysis of collagen, elastin and lysyl oxidase expression in breast capsular contracture - Poh, Patrina S. P. (2018)
Background: Capsular contracture is one of the most common complications in surgical interventions for aesthetic breast augmentation or post-mastectomy breast reconstruction involving the use of silicone prostheses. Although the precise cause of capsular contracture is yet unknown, the leading hypothesis is that it is caused by long-term unresolved foreign body reaction towards the silicone breast implant. To authors’ best knowledge, this is the first study that elucidates the presence of lysyl oxidase (LOX)—an enzyme that is involved in collagen and elastin crosslinking within fibrous capsules harvested from patients with severe capsular contracture. It was hypothesized that over-expression of LOX plays a role in the irreversible crosslinking of collagen and elastin which, in turn, stabilizes the fibrous proteins and contributes to the progression of capsular contracture. Methods: Eight fibrous capsules were collected from patients undergoing capsulectomy procedure, biomechanical testing was performed for compressive Young’s moduli and evaluated for Type I and II collagen, elastin and LOX by means of non-linear optical microscopy and immunohistology techniques. Results: Observations revealed the heterogeneity of tissue structure within and among the collected fibrous capsules. Regardless of the tissue structure, it has been shown that LOX expression was intensified at the implant-to-tissue interface. Conclusion: Our results indicate the involvement of LOX in the initiation of fibrous capsule formation which ultimately contributes towards the progression of capsular contracture.